Pendayagunaan Fasum melalui Urban Farming dalam Meningkatkan Kesejahteraan Ekonomi Keluarga di Desa Pabean - Insyirah Putikadea; Ika Permatasari; Amirusholihin Amirusholihin; Ariel Rendra Pratama; Dhita Berliana Tri Rahmawati Rawi (Pusat Riset dan Inovasi Nasional, 2025)
This community service program aims to empower the residents of Pabean Village, particularly community members of Family Welfare and Women Empowerment Organisation (PKK) RW 15, by utilizing narrow and non-productive public facilities land through the implementation of urban farming systems through aquaponic method. The activities are designed with a participatory-based capacity-building approach that emphasizes active community involvement at every stage, from outreach, training, technology implementation, to sustainable assistance and monitoring. The results of the activities show a significant improvement in the aspects of knowledge, skills, and participatory attitudes of the community. The average pre-test score of 92.3 increased to 97.9 in the post-test for technical capabilities in urban farming methods, while financial managerial skills increased from 83.3 to 90.6. In addition, 90% of participants expressed their commitment to implementing urban farming by maintaining the aquaponic installation, and 70% felt capable of transferring the skills to other participants. This program successfully transformed public facility land into productive green spaces as sources of food (fresh vegetables and fish), providing education and skills as a part of social activities. These impact on increasing solidarity, a sense of joint-ownership, and economic independence among members of the PKK. Thus, community-based urban farming has proven effective in promoting social transformation, enhancing food security, and improving family economic welfare.